The impact of online use of English on motivation to learn. Issue 1 (2nd January 2020) - Lamb, Martin; Arisandy, Fauziah Eka
Abstract: Profound changes in the literacy practices of young people in the early part of this century mean that many are encountering and using English in their personal lives while studying the language formally in school or university, potentially shaping their language development and attitudes. This article reports a research project which investigated how metropolitan youth in Indonesia were using English online, how this related to their global motivation to learn English, and in particular how it related to their attitudes to classroom English lessons. A mixed method design included a 56-item survey of students at a leading university ( n  = 308) and follow up interviews with four participants who showed different profiles of activity and motivation. Levels and type of online activity were broadly in line with findings in other contexts, with students favoring entertainment and self-instruction rather than socially-oriented activity; this correlated broadly with a positive attitude to classroom learning, but cluster analysis showed that some individuals exhibited a different pattern of response which was explored in interview. The article discusses ways in which teachers of learners at lower levels of proficiency, operating under major curriculum constraints, may integrate learners' online informal learning of English into their classroom practice, and how teacher educators might help them do this.